Pharmacognostic and Toxicity Evaluation of Tabar Kedayan (Aristolochia papilifolia Ding Hou) Rootstock - Lestari, Seftya Ayu; Iswahyudi, Iswahyudi; Arifuddin, M.; Prabowo, Wisnu Cahyo; Ahmad, Islamudin (Journal of Pharmaceuticals and Natural Sciences, 2025)
Tabar kedayan (Aristolochia papillifolia Ding Hou.) is an endemic plant from northern Kalimantan and is widely used as traditional medicine by the Dayak people. This study aims to determine the pharmacognostic profile and toxicity data of Tabar Kedayan rootstock. The results showed macroscopically woody stem type, round stem shape, grooved or serrated stem surface, yellow-brown stem color, weak characteristic odor, bitter taste, microscopically found starch grains, calcium oxalate crystals, stone cells, cork cells, tracheids, and wood vessels. Fluorescence analysis under visible and ultraviolet light for Tabar Kedayan rootstock powder with different chemical reagents showed different fluorescence effects. Water content (0.466±0.01%), ethanol content (0.325±0.014%), moisture content (12.40±0.15%), total ash content (1.438±0.15%), and acid insoluble ash content (0.423±0.06%). Phytochemical screening of the chemical compounds of the ethanolic extract showed the presence of alkaloids, terpenoids, saponins, flavonoids, and tannins. The levels of total polyphenols (15.095 ± 1.11 µg GAE/mg sample), total flavonoids (0.184 ± 0.02 µg QE/mg sample), and total alkaloids (0.056 ± 0.02 µg QAE/mg sample) were found. The brine shrimp lethality (BSLT) assay results showed the highest LC50 value by the n-hexane fraction with an LC50 value of 17.660 µg/ml.